2014
DOI: 10.5530/pj.2014.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of phyllanthin and hypophyllanthin after oral administration to rats

Abstract: Objective: The present study was carried out to develop a sensitive and cost effective HPLC method for the determination of bioactive lignans (phyllanthin and hypophyllanthin) and its application in a pharmacokinetic study. Methods: Identification of lignan compounds on C-18 column was monitored at a range of 199-400nm using photodiode array detector (PDA) with methanol-water (66:34, v/v) as mobile phase at a flow rate of 1ml/min. Carbamazepine was used as internal standard. Results: From the developed method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In our method, the LLOQ was only 0.5 ng/ mL, compare with HPLC-FD method, 10 the LOQ was 4.88 ng/mL, our method was almost 10 times more sensitive than this HPLC-FD method. In the report of Madhukiran et al 11 , the LOQ of phyllanthin was up to 169.99 ng/mL wih the use of HPLC-PDA, our method demonstrated up to 340 times more sensistive than HPLC-PDA method.…”
Section: Calibration Curvementioning
confidence: 59%
See 2 more Smart Citations
“…In our method, the LLOQ was only 0.5 ng/ mL, compare with HPLC-FD method, 10 the LOQ was 4.88 ng/mL, our method was almost 10 times more sensitive than this HPLC-FD method. In the report of Madhukiran et al 11 , the LOQ of phyllanthin was up to 169.99 ng/mL wih the use of HPLC-PDA, our method demonstrated up to 340 times more sensistive than HPLC-PDA method.…”
Section: Calibration Curvementioning
confidence: 59%
“…6 Furthermore, phyllanthin is known to possess immunomodulatory 7 , nephroprotective 8 , and anticancer 9 properties. Pharmacokinetic study of phyllanthin after oral administration to rats showed that phyllathin can be absorbable via GI tract 10,11 , however, the bioavailability of phyllanthin was only 0.62% in rat 12 . Because the content of phyllanthin in herb or herb extract is very low, and this herbal drug was used as a total extract, not a single pure compound of phyllanthin, it is important to quantitate such a low level of phyllanthin in the blood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Thanh et al (2014Thanh et al ( ) et al, 2013Parvathaneni et al, 2014b;Van Thanh et al, 2014), hepatoprotective (Syamasundar et al, 1985;Harish and Shivanandappa, 2006;Rajkapoor et al, 2008;Taesotikul et al, 2011;Srirama et al, 2012;Subramanian et al, 2019;Wahyuni et al, 2019), anti-hyperuricemic (Murugaiyah and Chan, 2006), vascular tension (Hussain et al, 1995;Inchoo et al, 2011), estrogenic (Islam et al, 2008a) and anti-allergic activities (Abd Rani et al, 2021).…”
Section: Methanolmentioning
confidence: 99%
“…In vivo and in vitro studies on the pharmacological activities of hypophyllanthin include immunomodulation, anti-inflammatory, anticancer, hepatoprotective, anti-hyperuricemic, vascular tension, and anti-allergic activities. Figure 3 ; Tables 2 , 3 shows the various pharmacological activities of hypophyllanthin as a major component in the extracts of Phyllanthus species such as immunomodulation ( Jantan et al, 2014 ; Harikrishnan et al, 2018a ; Harikrishnan et al, 2018b ; Harikrishnan et al, 2018c ), anti-inflammatory ( Rachmilewitz et al, 1989 ; Mali et al, 2011 ; Kandhare et al, 2013 ; Chopade and Sayyad, 2015 ; Ilangkovan et al, 2015 ; Pradit et al, 2015 ; Wu et al, 2019 ), anticancer ( Somanabandhu et al, 1993 ; Islam et al, 2008b ; Sukhaphirom et al, 2013 ; Parvathaneni et al, 2014b ; Van Thanh et al, 2014 ), hepatoprotective ( Syamasundar et al, 1985 ; Harish and Shivanandappa, 2006 ; Rajkapoor et al, 2008 ; Taesotikul et al, 2011 ; Srirama et al, 2012 ; Subramanian et al, 2019 ; Wahyuni et al, 2019 ), anti-hyperuricemic ( Murugaiyah and Chan, 2006 ), vascular tension ( Hussain et al, 1995 ; Inchoo et al, 2011 ), estrogenic ( Islam et al, 2008a ) and anti-allergic activities ( Abd Rani et al, 2021 ).…”
Section: Pharmacological Activities and Mechanisms Of Actionmentioning
confidence: 99%